ASBAL DALAM TAREKAT NAQSYABANDIYAH DI KOTA PONTIANAK (KHAZANAH RITUAL SUFISTIK) - Rahimi, Muhammad (The Pontianak State Institute of Islamic Studies, 2012)
Many people hold a negative perception of the existing tarekat (path for mystics to follow especially Sufism). This attitude is the result of the exclusiveness of the tarekat’s programs. One of the exclusive programs is the asbal activity in the tarekat of Naqsyabandiyah Muzhariyah in Pontianak. Besides, in the asbal activity rebana (tambourine) is used to accompany praise to Rasulullah (Messenger of God) which allows of many interpretations among the society. However, it can be explained that the exclusiveness of the asbal activity is aimed at avoiding suspicion in conducting tarekat which may result in bid’ah and the practice of tarekat without bai’at. The asbal activity also contain aspects of collective guidance which will further be elaborated in this writing.